Biosynthetic nanobubbles for targeted gene delivery by focused ultrasound. Issue 31 (26th July 2019) - Tayier, Baihetiya; Deng, Zhiting; Wang, Yu; Wang, Wei; Mu, Yuming; Yan, Fei
Abstract : Cationic biosynthetic nanobubbles combined with ultrasound lead to significantly improved gene transfection efficiency. Abstract : Ultrasound-targeted microbubble destruction (UTMD) has recently drawn considerable attention in biomedicine applications due to its great potential to locally enhance gene delivery. However, conventional microbubbles have a microscale particle size and polydisperse particle size distribution, which makes it difficult for them to directly come into contact with tumor cells and to efficiently deliver therapeutic genes via ultrasound cavitation effects. In the current study, we developed a kind of novel cationic biosynthetic nanobubble (CBNB) as an ultrasonic gene delivery carrier through coating PEI on the surface of these biosynthetic nanobubbles (BNBs). The BNBs, produced from an extremely halophilic archaeon ( Halobacterium NRC-1 ), possess a nanoscale size and can produce stable contrast signals both in vitro and in vivo . Surface modification with PEI polymer greatly increased the DNA loading capability of BNBs, leading to significantly improved gene transfection efficiency when combining with ultrasound. To our knowledge, this is the first report to apply biosynthetic bubbles as non-viral gene carriers which can effectively deliver genes into tumor cells with the aid of ultrasound cavitation. Our study provides a powerful tool for image-guided and efficient gene delivery using biosynthetic nanoscale contrast agents.